Coexistence of T-Large Granular Lymphocyte Leukemia and Peripheral T Cell Lymphoma-NOS with indolent behaviour - Luca Guarnera; Valentina Boldrini; Gianmario Pasqualone; Carolina Cimino; Elisa Meddi; Roberta Laureana; Donata Trivigno; Giovanni Del Poeta; Alessandro Mauriello; Lucia Anemona; Massimiliano Postorino; Maria Cantonetti (Mediterranean Journal of Hematology and Infectious Diseases)
T-cell lymphomas and leukemias are highly heterogeneous groups of rare disorders. We report a case of a 68-year-old man patient who develops two different T-cell neoplasms (Large Granular Lymphocyte Leukemia [LGLL] in 2018 and Peripheral T-cell non-Hodgkin lymphoma  not otherwise specified [PTCL-NOS] in 2019) with a previous diagnosis of B-cell marginal zone lymphoma in 2010, treated with two lines of chemo-immunotherapy. The coexistence of these different T-cell neoplasms is rarely reported in literature and, moreover, is usually described as an LGLL transformation into PTCL-NOS; differently from these examples, herein the simultaneous conditions appear to be driven by different T-cell clones. Furthermore, the PTCL-NOS had a quite unusual behaviour, with a good disease control without intensive treatment. Because of these features, it could belong to a subgroup of indolent PTCL-NOS, not yet described in the WHO classification of T-cell neoplasms, which could benefit of less aggressive treatment.